Maternal exposure to PM2.5 may increase the risk of congenital hypothyroidism in the offspring: a national database based study in China - Li Shang; Liyan Huang; Wenfang Yang; Cuifang Qi; Liren Yang; Juan Xin; Shanshan Wang; Danyang Li; Baozhu Wang; Lingxia Zeng; Mei Chun Chung (BMC, 2019)
Abstract Background Maternal exposure to air pollution is related to fetal dysplasia. However, the association between maternal exposure to air pollution and the risk of congenital hypothyroidism (CH) in the offspring is largely unknown. Methods We conducted a national database based study in China to explore the association between these two parameters. The incidence of CH was collected from October 1, 2014 to October 1, 2015 from the Chinese Maternal and Child Health Surveillance Network. Considering that total period of pregnancy and consequently the total period of particle exposure is approximately 10 months, average exposure levels of PM2.5, PM10 and Air Quality Index (AQI) were collected from January 1, 2014 to January 1, 2015. Generalized additive model was used to evaluate the association between air pollution and the incidence of CH, and constructing receiver operating characteristic (ROC) curve was used to calculate the cut-off value. Results The overall incidence of CH was 4.31 per 10,000 screened newborns in China from October 1, 2014 to October 1, 2015. For every increase of 1 μg/m3 in the PM2.5 exposure during gestation could increase the risk of CH (adjusted OR = 1.016 per 1 μg/m3 change, 95% CI, 1.001-1.031). But no significant associations were found with regard to PM10 (adjusted OR = 1.009, 95% CI, 0.996-1.018) or AQI (adjusted OR = 1.012, 95% CI,0.998-1.026) and the risk of CH in the offspring. The cut-off value of prenatal PM2.5 exposure for predicting the risk of CH in the offspring was 61.165 μg/m3. Conclusions The present study suggested that maternal exposure to PM2.5 may exhibit a positive association with increased risk of CH in the offspring. We also proposed a cut-off value of PM2.5 exposure that might determine reduction in the risk of CH in the offspring in highly polluted areas.